Мифологический роман Лайоша Мештерхази «Загадка Прометея» - Александрова, О.Н. (Культура народов Причерноморья, 2014)
В статье Александровой О.Н. “Мифологический роман Лайоша Мештерхази «Загадка
Прометея»” (Mesterházi Lajos, настоящее имя – Hoefstedter Lajos, 1916–1979; «A Prométheusz – rejtély»,
1973) исследуется проблематика романа. В круг рассматриваемых проблем входят вопросы
традиционности трактовки образа Прометея от античности до наших дней и новаторство
венгерского романиста, связанное, прежде всего, с необычностью проблематики самого романа, в
котором Л. Мештерхази с позиций сегодняшней политики и современного литературоведения
трактует древний миф. Таким образом Мештерхази решает для себя чрезвычайно важные
политические и этические проблемы добра и зла, благодарности и безответственности, войны и мира,
государственной тирании и борьбы за мир и т.п. У статті Александрової О.М. "Міфологічний роман Лайоша Мештерхазі «Загадка
Прометея»" (Mesterházi Lajos, справжнє ім'я – Hoefstedter Lajos, 1916–1979; «A Prométheusz – rejtély» ,
1973) досліджується проблематика роману. У коло розглянутих проблем входять питання
традиційності трактування образу Прометея від античності до наших днів і новаторство угорського
романіста, пов'язане, насамперед, з незвичністю проблематики самого роману, в якому Л. Мештерхазі з
позицій сьогоднішньої політики і сучасного літературознавства трактує древній міф. Таким чином
Мештерхазі вирішує для себе надзвичайно важливі політичні та етичні проблеми добра і зла, подяки та
безвідповідальності, війни і миру, державної тиранії і боротьби за мир і т.п. In the Article by Alexandrova O.N. under the title «Mythological novel by Lajos Meshterhazi
"Prometheus Riddle"» the issues of the novel are explored. The novel of the Hungarian writer of the second half
of the twentieth century, Lajos Meshterhazi (Mesterházi Lajos, real name – Hoefstedter Lajos, 1916–1979)
«Prometheus Riddle» («A Prométheusz – rejtély», 1973) draws attention of the reading public worldwide. The
novelty of the research lies in an integrated approach to the study of the problems of the novel. The circle of the
challenges includes the questions of the traditional interpretation of the image of Prometheus, starting with
antiquity to the present day, the innovations of the Hungarian novelist associated primarily with the unusual
perspective of the novel itself, in which L. Meshterhazi treats ancient myth from the standpoint of nowadays
polities and modern theory of literature. Thus, L. Meshterhazi decides for himself extremely important political
and ethical issues of good and evil, gratitude and irresponsibility, war and peace, the state of tyranny and the
struggle for peace, etc. The article discusses the features of L. Meshterhazi interpretation of the mythological
image of titanium Prometheus. Besides, in the works of the writer, who is the member of the Communist Party
and the participant of Hungarian Resistance the problems retreat from the traditions of socialist realism and the
principle of partisanship are raised. Writer’s search is mainly focused on the moral character of a person, her
concern are the issues of social morality and ethics, he with their help treats all the major social conflicts of the
era of building socialism, his works, in the best sense of the word, are publicistic, saturated with burning issues
of the contemporary world.